Drugs Run In The Body Effects On Biochemical Processes - Oblokulov Shavkat Shaimovich (Zien Journals, 2022)
When a person takes a substance with narcotic qualities, it alters the biochemical processes that occur in his body. Changes in hormone synthesis, which regulate the course of biochemical reactions, occur, disturbing the organism's vital activity rhythm. The causes and implications of the foregoing conditions are discussed in this article, as well as the history of human knowledge and drug use in ancient times, and ancient scientists' perspectives on drug-containing plants. Some drugs with narcotic characteristics are currently employed in medicine. There are also instances of drug misuse that are not medically related. The repercussions of drug addiction, the reasons that produce it, and the different sorts of drugs are all discussed in this article
Keywords: drugs; cannabis; hashishism; tetrahydrocannabinol